2022
DOI: 10.1071/wf21150
|View full text |Cite
|
Sign up to set email alerts
|

Can ash from smoldering fires increase peatland soil pH?

Abstract: Peatland wildfire frequency and severity are increasing globally owing to climate change. The direct risk of elevated greenhouse gas emissions from peat burning receives much attention, yet the risks to vegetation composition or peat decomposition from alkaline ash inputs are poorly understood. We explored whether ash produced during smoldering increases peatland topsoil (∼0–25 cm) pH through field observations and laboratory experiments. We assessed spatial patterns of smoldering and ash presence, and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
3
12
1
1
Order By: Relevance
“…From the soil science perspective, meaningful fire' impact was undergone on the N, P, and base cations, as shown by their huge content/concentrations after being burned compared to unburned peat, in agreement with other reports (Dhandapani & Evers, 2020), except for organic C and N contents. Meanwhile, pH increments in both depths at burned peat were not as high as hypothesized, similarly to the findings in subtropical (Marcotte et al, 2022) and tropical (Sulaeman et al, 2021) peatlands. However, the pH ranges at the burned sites presented in this study were much lower than those reported in burned Malayan peatland, North Selangor, either when peat was sampled in the wet or dry season (Dhandapani & Evers, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…From the soil science perspective, meaningful fire' impact was undergone on the N, P, and base cations, as shown by their huge content/concentrations after being burned compared to unburned peat, in agreement with other reports (Dhandapani & Evers, 2020), except for organic C and N contents. Meanwhile, pH increments in both depths at burned peat were not as high as hypothesized, similarly to the findings in subtropical (Marcotte et al, 2022) and tropical (Sulaeman et al, 2021) peatlands. However, the pH ranges at the burned sites presented in this study were much lower than those reported in burned Malayan peatland, North Selangor, either when peat was sampled in the wet or dry season (Dhandapani & Evers, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, we speculated that their study was conducted in the peat area that experienced a relatively immense magnitude and more severe fire than both Sulaeman et al, 2021 and our sites. In addition, a high temperature was observed during peat combustion (~400 to 600°oC), causing the smoldering process and resulting in ash with higher pH (Quintana et al, 2007;Rein et al, 2008;Úbeda et al, 2009;Marcotte et al, 2022). We believe that the combination of the sampling method with the smoldering effect and higher ash' pH was why more burnedaged surface peat from Dhandapani and Evers (2020)' site had extremely high pH and soil nutrients concentration compared to our results.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations